An exploration of the potential benefits of integrated pest management systems and the use of insect resistant potatoes to control the Guatemalan Tuber Moth (Tecia solanivora Povolny) in Ventaquemada, Colombia - Falck-Zepeda, José B.; Barreto-Triana, Nancy; Baquero-Haeberlin, Irma; Espitia-Malagón, Eduardo; Fierro-Guzmán, Humberto; López, Nancy (International Food Policy Research Institute, 2006)
CORPOICA and IFPRI implemented a research project in Ventaquemada, Colombia. The project’s goal was to asses the benefits of Integrated Pest Management (IPM) practices and the potential of Genetically Modified insect resistant (Bt) potatoes to manage damage caused by the Guatemalan Tuber Moth (Tecia solanivora Povolny). The Guatemalan Tuber Moth is particularly destructive because field spraying on the adult stage is ineffective and there exists damage specificity to the tubers. Excessive pesticide sprays have resulted in resistance to several insecticides. Insect resistant (Bt) potatoes has been shown an effective means to control other members of the Tuber Moth complex. Thus a Bt potato may play a role in managing Tecia in Colombia. This is an ex ante study as there are no Bt potatoes currently under field conditions in Colombia.. To examine this issue, we conducted a survey in 2003 of 78 farmers in the region to estimate a baseline of traditionally and IPM managed systems. The first year survey was supplemented with focus groups to examine damage and production costs in 2003 and 2004. We also implemented activities such as field verification of IPM practices and damage, a Farmer Field School and other participatory methods. Our analysis uses methods such partial budgeting analysis, a production function input abatement expectations model, and an economic surplus model augmented by stochastic simulations. Results of the analysis presented here outlines estimated losses under field and storage conditions, likely range of benefits accrued by farmers in the region due to the potential adoption of a portfolio of IPM management practices and Bt potatoes. Results from the survey conducted in 2003 show that producers in the area have endured significant field and storage losses within the previous 10 years, but were low in that particular year. Initial results where confirmed by results of focus groups in 2003 and 2004 which show very low field and storage damage. Sustained precipitation explains the observed low levels of damage by the Tuber Moth. Low levels of damage induced zero (or even negative) cost differences between conventional and IPM management. In contrast, using the proposed expectation model to estimate expected payoffs to IPM investments show that even with low levels of damage it still pays for producers to invest in IPM practices. The economic surplus estimates show that even considering variability of field and storage losses, as well as of other critical parameters, the use of Bt potatoes in Colombia creates a positive return to investment to Bt potato research, assuming that damage is present under field conditions. We finalize by discussing some of the institutional and strategic considerations for the potential use of Bt potatoes in the country.